(untitled) - Naborov, Vladimir Vladimirovich (New York, NY, 1996)
Nabokov's novels, Novels 1955-1962 contains his most acclaimed and popular works. The short, often anthologized Pnin is included, as is Pale Fire, Nabokov's most elaborate fictional joke: it's a novel masquerading as a 999-line poem accompanied by a professorial pedant's extensive annotations. But this deluxe volume is most valuable for its inclusion of Lolita alongside the screenplay that Nabokov wrote for Stanley Kubrick. Kubrick's film is quite different from the version Nabokov intended, and Novels 1955-1962 offers the opportunity to compare Lolita's two Nabokovian incarnations with Kubrick's film and with the recent, very controversial movie directed by Adrian Lyne and starring Jeremy Irons
Keywords: American literature,American fiction,Naborov, Vladimir Vladimirovich, 1899 - 1977; 20th century,20th century